Food and nutrient intake in Spanish vegetarians and vegans. - Menal-Puey, Susana; Morán del Ruste, Manuel; Marques-Lopes, Iva (Progress in Nutrition, 2018)
Objective: Vegetarian and vegan diets have gained popularity in Spain. There is no available information about specific food, supplementary intake and macro and micronutrient profile in Spanish ve-getarian population. This study aimed to determine and evaluate their dietary intake. Methods: One hundred two Spanish vegetarian and vegans completed a food frequency questionnaire from which their specific food consumption as well daily intake of macro and micronutrients was assessed and subsequently compared to Spanish Dietary Reference intakes. Results: In both groups the diet appeared well balanced with a healthy distribution of macronutrients and fatty acids and a high content of fiber. Vegan subjects showed higher intakes of vegetables, nuts and seeds as compared to vegetarians. At micronutrient level, almost all the vitamins and minerals intake covered Spanish Dietary Reference intakes. Intakes of vitamin B12 and D were below recommendations in both groups. In those micronutrients with a lower intake, higher proportions of vegetarians did meet recommendations as compared to vegans. Conclusions: Diet appeared well balanced regarding macronutrients and fiber. Almost all of the vitamins and mineral intake covered the Spanish DRIs, except B12 and D. Further studies with a large sample are needed to establish conclusions to the Spanish vegetarian population.